Antimicrobial use and antimicrobial resistance: standpoint and prescribing behaviour of Italian cattle and pig veterinarians. Issue 1 (14th December 2020) - Pozza, G.; Pinto, A.; Crovato, S.; Mascarello, G.; Bano, L.; Dacasto, M.; Battisti, A.; Bartoli, B.; Ravarotto, L.; Marangon, S.
Abstract: The scientific community considers the improper use of antimicrobials in farm animals among the causes of the insurgent bacterial resistance contributing to the wider pool of resistance at the animal/human interface with serious public health implications. The present study aims to describe the current perceptions regarding antimicrobial use (AMU) and resistance (AMR) and the prescribing behaviour of two different target groups: cattle and pig veterinary practitioners working in Italy. A semi-structured questionnaire was designed and administered using the Computer-Assisted Web Interviewing method. Among the 789 participants who completed the questionnaire, 53.5% and 12.2% were cattle and pig veterinarians, respectively. Differences between the two groups emerged in their opinions concerning different topics. For example, 69.4% and 85.8% of cattle veterinarians claimed to 'somewhat or strongly agree' with the statements 'prescribing broad-spectrum antibiotics in rearing farms increases AMR' and 'the preventive use of antibiotics fosters the development of AMR', against the observed 59.4% and 69.8% of pig veterinarians ( p = .050 and p = .000, respectively). Moreover, 26% of pig veterinarians claimed to 'somewhat or strongly agree' with the statement 'alternative methods currently available could be an efficient alternative to antimicrobial treatment', against 16.1% of cattle veterinarians ( p = .022). At the same time, no differences between the two groups emerged regarding the danger inadequate AMU in animals poses on both animal and human health. From collected data, the need to provide appropriate training strategies with the aim of adopting a behaviour more consistent with the guidelines for prudent AMU in cattle and pig production systems has emerged. HIGHLIGHTS: 85.8% of cattle vs. 69.8% of pig veterinarians agreed with the statement 'the preventive use of antibiotics fosters the development of AMR'. 64.5% of cattle and 69.1% of pig veterinarians declared they suggest/prescribe alternative approaches to the use of antimicrobials. 'Hygiene-biosecurity-management' and 'nutritive principles' are the alternative strategies most suggested by cattle and pig veterinarians, respectively.